Persepsi Klien Diabetes Mellitus terhadap Fungsi Seksual - Detiana Detiana; Abdul Somad; Yunike Yunike; Ira Kusumawaty; Dita Yurizmah; Qana’ah Qana’ah; Elisa Martabaya; Alda Denada (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify the perceptions of clients with diabetes mellitus towards fulfilling sexual needs in the internal medicine polyclinic at Lahat Hospital. The research method used was a quantitative method with a cross-sectional approach and focused on this study, male clients with diabetes mellitus. This activity was carried out by distributing questionnaires at the Lahat Hospital in South Sumatra Province on 22 - 24 September 2022 with the appropriate respondent criteria. From the results of the study, it was found that people with diabetes mellitus were in the age range of 51-59 years. The results of the study showed that 93% of the respondents perceived sexual function disorders, the respondents who supported sexual function were quite large, namely 75%. Respondents who perceive no interference with sexual function, namely 40%, are due to a counter culture or deviation from cultures. The conclusion of this study is that meeting the sexual needs of people with diabetes mellitus cannot be ignored and to prevent erectile dysfunction in people with diabetes mellitus, it is necessary to pay attention to regular blood sugar control and dietary adjustments. Keywords: Diabetes Mellitus, Erectile Dysfunction, Perception